Norepinephrine Versus Phenylephrine for the Prevention of Post Spinal Hypotension in Cesarean Section - Thapa, Nabin; Vaidya, Pradip Raj; Shrestha, Sangeeta; Thapa, Savina (Journal of Karnali Academy of Health Sciences, 2022)
Background: Hypotension following spinal anesthesia in the cesarean section is common despite adequate fluid loading. The recommended medication to treat spinal hypotension during cesarean section is phenylephrine. Norepinephrine bolus has recently been proposed as an alternative to phenylephrine bolus. Our study's objective was to evaluate the efficacy of bolus doses of phenylephrine and norepinephrine in treating spinal-induced hypotension after cesarean delivery.Methods: One hundred and eighty parturient, ASA II, aged above 18 years, planning an elective cesarean section under anesthesia were randomly assigned by the lottery method into the two groups. Group P received Phenylephrine 50 µg intravenous bolus, and Group N received 5 µg of Norepinephrine intravenous bolus to prevent spinal-induced hypotension.Results: The incidence of hypotension after the prophylactic bolus dose of study drugs was 25.6% in group N and 32.2% in group P. The number of rescue bolus doses of the studied drug that were required to treat hypotension was lower in Group N than in group P (25.6% vs 32.2 % ). The Mephentermine that was required to treat hypotension was also lower in Group N than in Group P (11.1% vs 12.2 % ). The changes in heart rate and mean arterial pressure after the injection of the study drug were comparable.Conclusion: Prophylactic Norepinephrine and Phenylephrine bolus dose were equally effective in the prevention of spinal-induced hypotension during cesarean section.